Pemberdayaan masyarakat terhadap akibat hukum dalam penyalahgunaan narkotika di Desa Naumbai Kecamatan Kampar, Kabupaten Kampar, Provinsi Riau - Sukamarriko Andrikasmi; Emilda Firdaus; Dessy Artina; Mexsasai Indra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Community empowerment in an effort to prevent narcotics abuse is needed to protect the nation's future generations, thus it will help create a great community and independent village and will be able to create more creativity and wider work. The problem that occurs is community empowerment against the legal consequences of narcotics abuse in Naumbai Village, Kampar District, Kampar Regency, Riau Province. The purpose of community service activities that will be carried out is to provide knowledge and understanding of the importance of staying away from narcotics so as to create a healthy and creative society. The benefits are expected to have a good impact in terms of health, economy and social so that women can help the family economy and village communities, so that the people of Naumbai Village, Kampar District, Kampar Regency, Riau Province can obey and obey the law and are not involved in narcotics abuse.